An ethnographic study exploring the experiences of patients living with cancer illness in support group settings in KwaZulu-Natal, South Africa - Nkosinathi Mncwabe; Khumbulani W. Hlongwana; Themba G. Ginindza (AOSIS, 2021)
Background: The major strength of support groups stems from their ability to help patients manage their health within and outside the traditional hospital settings. Despite the known benefits of support groups for people living with cancer, ethnographic studies documenting the cancer patients' experiences of living with cancer within the support group contexts in KwaZulu-Natal are scarce. Aim: The aim of this study was to examine the experiences of patients living with cancer within a support group setting. Setting: The study setting was support groups in KwaZulu- Natal, South Africa. Materials and Methods: This study was conducted using, participant observation, focus group discussions and in-depth interviews. Data were generated over a 3-month period. Purposive sampling was used to identify the information-rich participants. Thematic data analysis was performed in order to obtain insights into the collective meaning of data generated. Results: Participants viewed the support group settings as creating an environment with a unique sense of community. This was in contrast with the sense of isolation, rejection and lack of empowering knowledge on cancer, often experienced outside these contexts. Moreover, the support groups were lauded for facilitating positive relationships with family and friends and providing a safe space for members to freely express their emotions. Conclusion: Psychosocial support provided by support groups can help to ameliorate the distress caused by cancer diagnosis and its treatment; however, these support groups are still few and far in between. Therefore, there should be a greater investment in establishing support groups.